2004
DOI: 10.1021/ja048775l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Compressed Dihydride Complexes of Iridium:  Theoretical and Spectroscopic Investigations

Abstract: Reaction of [Cp*Ir(P-P)Cl][B(C6F5)4] (P-P = bisdimethydiphosphinomethane (dmpm), bisdiphenyldiphosphinomethane (dppm)) with [Et3Si][B(C6F5)4] in methylene chloride under 1 atm of hydrogen gas affords the dicationic compressed dihydride complexes [Cp*Ir(P-P)H2][B(C6F5)4]2. These dicationic complexes are highly acidic and are very readily deprotonated to the corresponding monohydride cations. When the preparative reaction is carried out under HD gas, the hydride resonance exhibits JHD = 7-9 Hz, depending upon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
79
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 29 publications
14
79
1
Order By: Relevance
“…[8] In this study it was found that 1 J HD depended not only on R HÀH , as is well known, but also that it has a certain dependence on R MÀH 2 . Hence we think it is preferable, if possible, to compute 1 J HD directly and compare it to experimental data, especially since it has been previously demonstrated in several cases of elongated dihydrogen/compressed dihydride complexes that MÀH 2 and HÀH motions are inextricably coupled.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…[8] In this study it was found that 1 J HD depended not only on R HÀH , as is well known, but also that it has a certain dependence on R MÀH 2 . Hence we think it is preferable, if possible, to compute 1 J HD directly and compare it to experimental data, especially since it has been previously demonstrated in several cases of elongated dihydrogen/compressed dihydride complexes that MÀH 2 and HÀH motions are inextricably coupled.…”
Section: Resultssupporting
confidence: 60%
“…However, as is known for this family of complexes, the experimentally resolved geometry cannot be compared directly to that of a direct minimization of the potential energy, as is customary with most other systems, because the flatness of the potential energy surface describing the motion within the MÀH 2 unit makes it necessary to consider nuclear motion quantum dynamically. Thus, following the same procedure as in previous studies [4,29,8] we determined the relaxed potential energy surface as a function of HÀH and MÀH 2 stretches, which are represented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value for the H-D coupling constant is consistent with the formation of the trans isomer. [23] Interestingly, in addition to the resonance of complex [D]-2, the hydride resonance of complex 2 was also present in the 1 H NMR spectrum. Comparison of the integration value of the two hydride signals with the integration of the isopropyl CH resonance of the IPr ligand (3 vs. 12), strongly suggested the presence of the bis-deuterated complex [D 2 ]-2.…”
mentioning
confidence: 99%
“…[15] The partially deuterated analogue of complex 1 was prepared by 1 Ha nd 2 HNMR spectra are shown in Figure 2). This 1 J HD value corresponds to a d HH of 0.81 AE 0.02 .…”
mentioning
confidence: 99%